The political economy of shariah compliant ads on TV Al Hijrah. - Johori, Md. Rozalafri; Adzharuddin, Nor Azura; Yasin, Megat Al-Imran (2014)
Privatisation Policy (1983) has urged television (TV) stations to compete for their survival in generating income from advertising. Furthermore, this policy has imposed TV Al Hijrah in a dilemma because of its establishment as a non-profit TV station is based on Islamic Absorption Values Policy (1985), which was contained in Islam Hadhari Policy (2003). Therefore, this study attempts to comprehend the influence of political economy of Sharia compliant advertising of TV Al Hijrah for its strict and controlled conditions while increasing the advertising income. Based on the interview sessions with a producer and executive producer of TV Al Hijrah, the researchers found that, the influence of political economy is important towards the Interpretation of Sharia Compliant, Sharia Compliant Products and Social Responsibility Advertising. In conclusion, the influence of political economy towards Sharia compliant policy will strengthen the policy so that it can be understood as one of the Islamic requirements in Muslims daily life, including the publishing and viewing of the advertisements.